Subjective Well-Being Among Single Emerging Adults: The Roles Of Demographics, Satisfaction With Family, Friends, And Singlehood - Chong, Hoi Yan (2024)
Despite extensive research on subjective well-being (SWB), the experience and well-being of single emerging adults have received limited attention. This study addresses this gap by investigating the factors contributing to SWB in this population, particularly in the context of a delayed age of marriage in Malaysia.